“The Problem of Speech in Merleau-Ponty: My View of ‘Speaking Speech’ and ‘Spoken Speech’ in Light of Ontogenesis” - Rajiv Kaushik (Philosophies, 2025)
The turn away from phenomenology in 20th century French philosophy was in large part due to an increased emphasis on Ferdinand de Saussure’s notion of “linguistic structure”, i.e., that language is the internal system of differences between signs. Thinkers such as Paul Ricoeur and Jean-François Lyotard famously offered a “semiological challenge” to phenomenology. The idea was that phenomenology, especially Merleau-Ponty’s phenomenology, reduces to the sensible world and cannot think linguistic structure. Thus, the argument goes that phenomenology leaves out a basic element of human life: not only can it not think linguistic structure, but it also cannot think about elements, e.g., writing and text, which are its result. This paper takes up this challenge, especially in reference to Merleau-Ponty’s terminology in Phenomenology of Perception of “speaking speech” (parole parlante) and “spoken speech” (parole parlée). I point out that, in retrospect of his later work, Merleau-Ponty very clearly did want to take linguistic structure seriously. This, however, means that we need to reconsider some of the basic themes in his work. Taking inspiration from the recently published “problem of speech” lectures, I reconstruct Merleau-Ponty’s idea that speech is a concrete limit situation from which we get both the idea of a language structure in which there are differences and of an ontological difference between being and beings. This is an internal criticism of both linguistic structure and formal ontology. I begin the paper by noting that, in Merleau-Ponty’s descriptions of the tacit and spoken cogito, also in Phenomenology of Perception, Merleau-Ponty criticizes the notion of a subject to which language refers and highlights the notion of a subject that defies representational and denotational structure. I do not, however, go along with Merleau-Ponty’s own criticism of the tacit ego, which he ultimately declared too subjectivistic. Ultimately, I hope to stress the importance of linguistic structure and writing in Merleau-Ponty’s ontology. This is an ontology of that is fragile and requires symbolization. This paper emphasizes under-developed themes in Merleau-Ponty’s work such as bodily event, difference, symbolization, and the writing of philosophy.